Solubility Enhancement of Betamethasone, Meloxicam and Piroxicam by Use of Choline-Based Deep Eutectic Solvents - Salva Golgoun; Masumeh Mokhtarpour; Hemayat Shekaari (Tabriz University of Medical Sciences, 2021)
Background: The low aqueous solubility of three important drugs (betamethasone (BETA), meloxicam (MEL) and piroxicam (PIR)) have been increased by use of deep eutectic solvents (DESs) based choline chloride/urea (ChCl/U), choline chloride/ethylene glycol (ChCl/EG) and choline chloride/glycerol (ChCl/G) as new class of solvents at T = (298.15 to 313.15) K. Methods: DESs were prepared by combination of the ChCl/EG, U and G with the molar ratios: 1:2. The solubility of drugs in the aqueous DESs solutions was measured at different temperatures with shake flask method. Results: The solubility of the investigated drugs increased with increasing the weight fraction of DESs. The solubility data were correlated by e-NRTL and Wilson models. Also, the thermodynamic functions, Gibbs energy, enthalpy, and entropy of dissolution were calculated. Conclusion: At the same composition of co-solvents and temperature, the BETA, PIR and MEL solubility was highest in (ChCl/U + water), (ChCl/U + water) and (ChCl/EG + water) respectively. The calculated solubility based on these models was in good agreement with the experimental values. In addition, the results show that, the main contribution for drugs solubility in the aqueous DES solutions is the enthalpy.